Utilization of Passiflora tripartita fruit residues (Scientia Agropecuaria, 2021)
The seed and peel of the Passiflora tripartita fruit, have compounds of great importance that could be used by the agroindustry, pharmaceutical industry and medicine. This review article collects information on phenolic compounds, dietary fibers, and essential oils that fruit fractions have. The pulp of this fruit is intended for the preparation of antioxidant and additive functional beverages. The reports mention that the seeds have a high amount of polyunsaturated fatty acids, phenolic, and terpenes, and suggest being used in the form of nanoemulsions and as antimicrobials. Also, the terpenes in the essential oil of the seed have been linked to the treatment of colon cancer. Regarding the use of the peel, many species of the same genus are investigated for their antioxidant capacity, pectin content, dietary fiber and antimicrobial activity, having potential uses as antioxidant additives, enzymatic substrates, such as toothpaste, soaps, creams, and ingredient of animal feed.
Keywords: Passiflora tripartita; banana passion fruit; peel; seed; antioxidant activity; waste management